ANALISA TREN PEMANFAATAN CELEBRITY ENDORSEMENT: SEBUAH ULASAN LITERATUR SISTEMATIS (Faculty of Communications Science, Dr. Soetomo University, 2023)
This systematic literature review aims to analyze studies on the use of endorsement marketing by celebrities. The data comes from several sources from Crossref collected between 2020 and 2022. Keywords used include